2017
DOI: 10.1109/tap.2017.2742556
|View full text |Cite
|
Sign up to set email alerts
|

Measured 21.5 GHz Indoor Channels With User-Held Handset Antenna Array

Abstract: For mobile systems involving hand held devices, the influence of the user on system performance has to be considered. Extensive studies below 6 GHz have demonstrated large effects on system performance. However, the impact of user influence at potential higher frequency bands for upcoming 5G mobile networks is still to be investigated. This work investigates how the user affects the performance of a 5G handset mock-up. The user impact is studied by channel sounding in an indoor scenario, with and without the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 38 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…An extensive campaign was performed in an indoor corridor scenario for both LOS and NLOS, as well as with and without a user holding the mock-up in a realistic grip [15]. The results confirmed that the human body might be detrimental to mmWave links by effectively blocking the dominant propagation paths, while in specific scenarios the body can act as an added scatterer, which can improve the link.…”
Section: A Examplesmentioning
confidence: 74%
See 1 more Smart Citation
“…An extensive campaign was performed in an indoor corridor scenario for both LOS and NLOS, as well as with and without a user holding the mock-up in a realistic grip [15]. The results confirmed that the human body might be detrimental to mmWave links by effectively blocking the dominant propagation paths, while in specific scenarios the body can act as an added scatterer, which can improve the link.…”
Section: A Examplesmentioning
confidence: 74%
“…To investigate this channel, real-time channel sounding is crucial. As an example, the described sounder was used to measure channels at 21.5 GHz between a two-port dual-polarized horn antenna and 7 microstrip patch antenna elements inside a mock-up handset, which was held and moved by a person, see [15]. The 2 × 7 MIMO channel was measured using a 1:7 switch with a CS duration of 41 µs for a single Rx element or 573 µs for all elements, corresponding to a maximum phase change for a plane wave of about 2 • or 15 • , respectively, assuming a speed of 1 m/s.…”
Section: A Examplesmentioning
confidence: 99%
“…At a channel (far-field) level, the shadowing effect of the human body compared to a simplified geometric model is evaluated in [7] with a comprehensive study on the blockage loss. The evolution of the received power from a handset when it is held with one hand by a real user is also measured in [8]. The main drawback of previous studies is the lack of repeatability or generalization of the conclusions to other grip positions or antenna arrays, i.e., usage conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many numerical studies characterized specific absorption rates (SAR) induced by the cellular phones . All those studies were carried out for cellular phones and only at their specific operating frequency bands, for example, 800/900, 1800/1900 MHz, and, more recently, at higher 5G frequencies …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] All those studies were carried out for cellular phones and only at their specific operating frequency bands, for example, 800/900, 1800/1900 MHz, and, more recently, at higher 5G frequencies. 13,14 Typical usage as well as the design and antenna features of wireless microphones are different from those of cellular phones and, consequently, the body effect is most likely to be different. Assessing the body loss for wireless microphones at different frequencies is of great importance for predicting their range of operation and when designing and installing wireless microphone systems.…”
Section: Introductionmentioning
confidence: 99%